Implementation of Green Accounting in the Manufacturing Sector and Its Implications for the Socio-Economic Resilience of Local Communities - Nenny Syahrenny (Perspectives on Advanced New Generations of Global and Local Economic Horizons, 2026)
This research addresses the critical conflict between manufacturing expansion and environmental degradation in Indonesia, where traditional accounting often fails to internalize social costs. Purpose: The study aims to evaluate how green accounting implementation influences local socio-economic resilience by testing the hypothesis that environmental cost transparency correlates positively with community welfare. Methods: Utilizing a quantitative causal-comparative design, the study analyzed secondary data from a purposive sample of 142 manufacturing firms listed on the Indonesia Stock Exchange (IDX) that participated in the Ministry of Environment and Forestry’s (KLHK) PROPER program between 2021 and 2024. Data were extracted from verified sustainability reports and official environmental audit scores, focusing on variables such as environmental protection expenditure (EPE) and local community investment indices. Results: Multiple linear regression analysis ( ) reveals that green accounting disclosure significantly boosts community resilience ( ), with firms achieving "Gold" PROPER ratings demonstrating 78.4% local labor absorption and superior infrastructure contributions. Implications: These findings suggest that integrating ecological costs into financial frameworks serves as a vital policy instrument for mitigating social conflict and enhancing corporate legitimacy. Conclusion: The study affirms that environmental transparency is essential for industrial sustainability, recommends standardized green audits by OJK and KLHK, and calls for longitudinal community happiness indices in future research.